Փիլոնի հայերեն թարգմանությունները և արդի փիլոնագիտությունը - Ռունիա, Դեյվիդ Թ. (Մատենադարան)
This paper, presented at the Matanedaran in Yerevan in October 2019, undertakes to give a survey of recent developments and trends in Philonic research as they relate to the Armenian corpus of treatises. First recent research on the writings themselves is examined, beginning with the philosophical treatises (Aucher vol. 1), followed by the exegetical writings, first those of which we still have the Greek text (Zarbhanalean), then those of which the Greek text is lost (Aucher vol. 2). Some brief comments are then devoted to recent commentaries on Philo’s works, particularly in the Philo of Alexandria commentary series (PACS). The paper then turns to recent trajectories in understanding Philo, focusing on the work of Maren Niehoff (an intellectual biography of Philo) and Greg Sterling (the context of Philo’s activities). Lastly attention is given to work on Philo’s reception in antiquity, with discussion of Metzler’s recent edition of Procopius’s Genesis commentary and of research on Philo in the Byzantine period, including medieval Armenia. The conclusion is that Philonic scholarship is flourishing, but that there remains much still to do, not least in the area of the reception of his writings and though․ В статье, представленной в виде доклада в Матенадаране в октябре 2019 года, нами предпринята попытка обзора новейших направлений в исследовании Филона в соотношении с армянским корпусом его сочинений. Во-первых, рассматриваются последние исследования самих его трудов: философских трактатов (изд. М. Авгеряна, т. 1), затем комментаторских трудов – как тех, греческие оригиналы которых сохранились (изд. Г. Зарбаналяна), так и тех, чьи оригиналы до нас не дошли (изд. М. Авгеряна, т. 2). Кратко останавливаемся на новейших комментариях к трудам Филона, в особенности в серии “Комментарии к Филону Александрийскому” (Philo of Alexandria commentary series: PACS). Затем мы обращаемся к сегодняшним путям понимания Филона, с особым вниманием к работе Марен Нихоф (составившей интеллектуальную биографию Филона) и Грега Стерлинга (изучающего социальный контекст деятельности Филона). Наконец, мы останавливаемся на исследованиях рецепции Филона в древности, с обсуждением новейшего издания комментария на книгу Бытия Прокопия Газского (Карен Метцлер) и исследованиях о Филоне в византийский период, включая средневековую Армению. Наш вывод – изучение Филона процветает, однако еще многое предстоит сделать, не в последнюю очередь – в области рецепции его трудов и мысли.
Keywords: Փիլիսոփայություն